Development and Evaluation of a Semi-automated Segmentation Tool and a Modified Ellipsoid Formula for Volumetric Analysis of the Kidney in Non-contrast T2-Weighted MR Images - Seuß, Hannes; Janka, Rolf Matthias; Pruemmer, Marcus; Hammon, Rebecca; Theis, Ragnar; Sandmair, Martin; Amann, Kerstin Ute; Bäuerle, Tobias; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Journal of Digital Imaging, 2017)
Volumetric analysis of the kidney parenchyma provides additional information for the detection and monitoring of various renal diseases. Therefore the purposes of the study were to develop and evaluate a semi-automated segmentation tool and a modified ellipsoid formula for volumetric analysis of the kidney in non-contrast T2-weighted magnetic resonance (MR)-images. Three readers performed semi-automated segmentation of the total kidney volume (TKV) in axial, non-contrast-enhanced T2-weighted MR-images of 24 healthy volunteers (48 kidneys) twice. A semi-automated threshold-based segmentation tool was developed to segment the kidney parenchyma. Furthermore, the three readers measured renal dimensions (length, width, depth) and applied different formulas to calculate the TKV. Manual segmentation served as a reference volume. Volumes of the different methods were compared and time required was recorded. There was no significant difference between the semi-automatically and manually segmented TKV (p = 0.31). The difference in mean volumes was 0.3 ml (95% confidence interval (CI), -10.1 to 10.7 ml). Semi-automated segmentation was significantly faster than manual segmentation, with a mean difference = 188 s (220 vs. 408 s); p < 0.05. Volumes did not differ significantly comparing the results of different readers. Calculation of TKV with a modified ellipsoid formula (ellipsoid volume × 0.85) did not differ significantly from the reference volume; however, the mean error was three times higher (difference of mean volumes -0.1 ml; CI -31.1 to 30.9 ml; p = 0.95). Applying the modified ellipsoid formula was the fastest way to get an estimation of the renal volume (41 s). Semi-automated segmentation and volumetric analysis of the kidney in native T2-weighted MR data delivers accurate and reproducible results and was significantly faster than manual segmentation. Applying a modified ellipsoid formula quickly provides an accurate kidney volume.
EVALuna2:14622

Improving diagnostic accuracy in assessing pulmonary edema on bedside chest radiographs using a standardized scoring approach - Hammon, Matthias; Dankerl, Peter; Voit-Hoehne, Heinz Leonhard; Sandmair, Martin; Kammerer, Ferdinand Josef; Uder, Michael; Janka, Rolf Matthias (BMC Anesthesiology, 2014)
To assess the value of a score-based system which allows standardized evaluation of pulmonary edema on bedside chest radiographs (CXRs) under routine clinical conditions.Seven experienced readers assessed bedside CXRs of ten patients with an extravascular lung water (EVLW)-value of <= 8 mL/kg (range: 4-8 mL/kg; indicates no pulmonary edema) and a series of ten patients with an EVLW-value of >= 15 mL/kg (range: 15-21 mL/kg; = indicates a pulmonary edema) with and without customized software which would permit a standardized assessment of the various indications of pulmonary edema. The software provides a score that identifies patients with and without pulmonary edema. EVLW-values were measured instantly after bedside CXR imaging using a pulse contour cardiac output (PiCCO) system and served as a reference standard. The patients were non-traumatic and not treated with diuretics or dobutamine during bedside CXR imaging and the PiCCO measurements. Mean sensitivity, specificity, positive and negative predictive value, the percentage of overall agreement and the free-marginal multirater kappa value was calculated for both the standard and the standardized score-based approach. The net reclassification index was calculated for each reader as well as for all readers.Evaluation of bedside CXRs by means of the score-based approach took longer (23 ± 12 seconds versus 7 ± 3 seconds without the use of the software) but improved radiologists' sensitivity (from 57 to 77%), specificity (from 90 to 100%) and the free-marginal multirater kappa value (from 0.34 to 0.68). The positive predictive value was raised from 85 to 100% and the negative predictive value from 68 to 81%. A net reclassification index of 0.3 (all readers) demonstrates an improvement in prediction performance gained by the score-based approach. The percentage of overall agreement was 67% with the standard approach and 84% with the software-based approach.The diagnostic accuracy of bedside CXRs to discriminate patients with elevated EVLW-values from those with a normal value can be improved with the use of a standardized score-based approach. The investigated system is freely available as a web-based application (accessible via: http://www.radiologie.uk-erlangen.de/aerzte-und-zuweiser/edema).
EVALuna2:14366

Semiautomatic segmentation of the kidney in magnetic resonance images using unimodal thresholding - Sandmair, Martin; Hammon, Matthias; Seuss, Hannes; Theis, Ragnar; Uder, Michael; Janka, Rolf Matthias (BMC Research Notes, 2016)
Total kidney volume (TKV) is an important marker for the presence or progression of chronic kidney disease, however, routine ultrasonography underestimates renal volume to a high and varying degree.The aim of this work was to adapt and evaluate a semi-automatic unimodal thresholding method for volumetric analysis of the kidney in native T2-weighted magnetic resonance (MR) images.In a group of healthy volunteers (n = 24; 48 kidneys), we defined a region of interest (ROI) by manually tracing the outline of the kidney in every MR image. An automatic unimodal thresholding algorithm with visual feedback was applied to the probability distribution function of voxel intensities in the ROI to remove intrarenal non-parenchyma volume. For comparison, reference volumes were created by manual segmentation. Intra- and inter-observer reliability was evaluated.There was a small, significant mean difference of 1.5 ml between semi-automatically and manually segmented TKV (p = 0.009, 95% CI [0.4, 2.7]). While intra-observer reliability was good (mean difference 2.9 ml, p < 0.01, 95% CI [1.5, 4.2]) there was a small but significant mean difference of 4.8 ml (p < 0.01, 95% CI [3.6, 5.9]) between the TKV results of different observers. Reference volume correlations were excellent (r = 0.97-0.98). Semi-automated segmentation was significantly faster than manual segmentation; mean difference = 234 s [91-483 s]; p < 0.05. Automatic unimodal thresholding removed a considerable mean volume of 18.7 ml (13.1%) from the coarse manual pre-segmentations.Unimodal thresholding of native MR images is a robust and sufficiently reliable method for kidney segmentation and volumetric analysis. The manual pre-segmentation can be done by non-experts with little introduction.
EVALuna2:14594